Jerome: Vita malchi introduction, text, translation, and commentary - Hieronymus, Sophronius Eusebius 345-420 (Oxford University Press, 2017)
A full translation and analysis of one of the more intriguing works by a figure who is central to our understanding of late antiquity and early Christianity: the translator, exegete, and controversialist Jerome (c.347-419/20AD)
Published in print: 2015
Published online: January 2017
Keywords: Malchus / Saint; Jerome / Saint / -419 or 420 / Vita Malchi Monachi captive; Hieronymus, Sophronius Eusebius -- 345-420 -- Vita Malchi; Kommentar